Changes in angular momentum during the tennis serve - Bahamonde, R. E. (Journal of Sports Sciences, 2000)
Three-dimensional cinematography and the direct linear transformation method were used to obtain the coordinates of the landmarks of five right-handed collegiate tennis players. A 15-segment model was used to calculate the total body angular momentum about three orthogonal axes (X, parallel to the baseline; Y, normal to baseline and pointing towards the net; and Z, pointing upwards) passing through the centre of mass and to obtain the segmental contribution of the trunk, arms and legs. Most of the clockwise angular momentum about the X-axis was concentrated in the trunk and the racket-arm. Between the events of maximum external rotation and ball impact, the clockwise angular momentum about the X-axis of rotation of most body segments was reduced and the racket-arm gained clockwise angular momentum. The body angular momentum about the Y-axis of rotation had two distinct patterns and was the result of the lateral rotation of the trunk as the racket shoulder was elevated in preparation for impact. This body angular momentum was clockwise from the event of maximum external rotation to impact for the players with the greatest ball speed, whereas it was counterclockwise for the other players. The angular momentum about the Z-axis of rotation was small and lacked a consistent pattern. The largest source of angular momentum in the tennis serve derives from the remote angular momentum about the X- and Y-axes of rotation, which are then transferred from the trunk to the racket-arm and finally to the racket. Near impact, most of the angular momentum (75.1%) was concentrated in the racket-arm. Of the angular momentum of the racket-arm, the largest percentages were concentrated in the racket (35.9%) and the forearm segment (25.7%).